Una Mirada Interseccional a la Violencia contra las Mujeres con Diversidad Funcional = An Intersectional Glance at Violence against Women with Functional Diversity - Conejo, Miriam Arenas (Oñati Socio-Legal Series, 2015)
The eradication of violence is one of the main demands of disabled women's organizations around the world. As a result of their activism, both the Beijing Platform for Action (1995) and the UN Convention on the Rights of Persons with Disabilities (2006) made specific mention of their greater risk of suffering violence and the need to implement appropriate measures. However, the countries that have included these recommendations in their laws against gender violence are still scarce. Moreover, according to some women with functional diversity, this invisibility is often reproduced both among the feminist and the disability rights movement. The aim of this paper is to explore how an intersectional approach could help to overcome this double obstacle: on the one hand, encouraging the creation of alliances between social movements working for similar objectives and on the other hand, developing legislation and public policies which do not reproduce the exclusion of traditionally marginalized social groups.